Sistem Informasi Persediaan Barang Pada Rumah Sakit Umum Daerah Kabupaten Batu Bara - Irfan Darmansyah (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
Rapid technological developments have encouraged society to adapt to advances in technology and information. One very important aspect of health services is the management of inventory in hospitals, which has a direct influence on the quality of services provided to patients. With the increasing number of patients and the complexity of health services in Batu Bara Regency, RSUD is required to have an effective system for managing inventory. Therefore, it is very important for Batu Bara District Hospital to develop and implement an effective inventory information system. This application has helped increase efficiency in making reports. Such as reports of incoming goods, outgoing goods, stock and mutation reports are faster and more efficient. Goods managers can easily access inventory information from anywhere and at any time. This has increased the accessibility of information and facilitated faster and more informed decision making.